(untitled) (Research, Society and Development, 2021)
This project aims to analyze the diagnostic methods, the most prescribed drugs and their indiscriminate use in suspected or confirmed cases of Covid-19 in the Agreste Pernambucano, as well as to analyze possible adverse drug reactions (ADR). Thus, when comparing the sensitivity of the three available tests, RT-PCR is considered the gold standard for Covid-19 diagnosis. Off-label use of drugs and self-medication have risen during the pandemic, which may cause adverse drug reactions, harmful and unintended responses at safe doses, due to its overuse. This is a descriptive-exploratory study, with a quantitative and qualitative approach. For the data collection, an invitation link to participate in an online questionnaire was sent to participants residing in the southern, central, and northern parts of the Agreste Pernambucano. The data was collected from July 20 to September 20, 2021 and 222 answers were considered valid. The results were organized in spreadsheets and illustrated in graphs and tables, 44 people chose to do the RT-PCR test, 42.8% of respondents said they self-medicated, the most prescribed drugs and used on their own were dipyrone, vitamin c, azithromycin and ivermectin, as a consequence of it was also observed unexpected reactions, such as hypotension, hypothermia, nausea, arrhythmia, among others. Therefore, it is of great importance that there should be awareness and education in health, in order to minimize the act of self-medication and its consequences. It is also necessary that the population and professionals notify in cases of ADRs.